2010
DOI: 10.3748/wjg.v16.i11.1409
|View full text |Cite
|
Sign up to set email alerts
|

Role ofBMP3in progression of gastric carcinoma in Chinese people

Abstract: Promotor region methylation of the BMP3 gene may cause gastric carcinoma in Chinese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In vitro studies have also suggested a role for BMP3 as a negative growth regulator in bone marrow progenitor cells through the inhibition of DNA synthesis and proliferation (16). Additionally, recent studies have revealed that BMP3 contributes to tumor development and progression (17)(18)(19). However, to the best of our knowledge, no study of a possible genetic association between polymorphisms in BMP3 and cancer has been conducted.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…In vitro studies have also suggested a role for BMP3 as a negative growth regulator in bone marrow progenitor cells through the inhibition of DNA synthesis and proliferation (16). Additionally, recent studies have revealed that BMP3 contributes to tumor development and progression (17)(18)(19). However, to the best of our knowledge, no study of a possible genetic association between polymorphisms in BMP3 and cancer has been conducted.…”
Section: Introductionmentioning
confidence: 87%
“…Although the role of BMP3 in the pathogenesis of cancer is unknown, several studies have demonstrated that BMP3 participates in the development of various types of cancer (17)(18)(19)(20)(21). Loh et al (17) reported that in colon cancer cell lines with methylation-dependent BMP3 downregulation, cell colony growth suppression was observed following the reintroduction of BMP3 coding sequences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations